Cuprous oxide-based nanocrystals with combined chemo/chemodynamic therapy to increase tumor drug sensitivity by reducing mitochondria-derived adenosine-triphosphate - Haoran He; Jiaming Wu; Min Liang; Yao Xiao; Xuejian Wei; Yuqin Cao; Zhiheng Chen; Tian Lin; Miaosheng Ye (Taylor & Francis Group, 2022)
Gastrointestinal (GI) tumor is a serious disease with high mortality rates and morbidity rates worldwide. Chemotherapy is a key treatment for GI, however, systematic side effects and inevitable drug resistance complicate the situation. In the process of therapy, P-glycoprotein (P-gp) could remove chemotherapy drugs from cells, thus causing multi-drug resistance. Chemodynamic therapy (CDT) utilizing Fenton chemistry has been used for cancer therapy, along with various combination therapies. The reactive oxygen species produced by CDT could inhibit P-gp's efflux pump function, which reduce chemoagents excretion and reverse drug resistance. In the present study, we developed novel nanocrystals (Cu2O@Pt NCs) to overcome drug resistance by reducing mitochondria-derived ATP through chemo/CDT in GI cancer. Furthermore, in vivo results in tumor-bearing mice demonstrated that treatment with Cu2O@Pt NCs with CDT and chemotherapy could achieve the most effective antitumor therapeutic effect with the least amounts of adverse effects. As a result, Cu2O@Pt NCs could provide a promising strategy for chemo/CDT-synergistic therapy.